2011
DOI: 10.1007/s12663-011-0282-1
|View full text |Cite
|
Sign up to set email alerts
|

Tubercular Ulcer: Mimicking Squamous Cell Carcinoma of Buccal Mucosa

Abstract: Tuberculosis is a chronic granulomatous disease that rarely affects oral cavity. Tuberculous lesions of the oral cavity are frequently overlooked in the differential diagnosis of oral lesions. The oral clinical presentation of tuberculosis may take many forms as ulcers, nodules, tubercular fissure, tubercular papilloma and tuberculomas. Diagnosis is confirmed by histopathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 14 publications
1
27
0
Order By: Relevance
“…Additionally, the clinical characteristics of the lesion aids in differentiating it from other pathologies in the oral mucosa such as syphilis, histoplamosis, planoepithelial cancer, or recurrent or aphthous stomatitis. [9][10][11] Our finding is related to that reported by Krawiecka and Szponar et al 14 and Erbaycu et al, 15 who considered that the clinical characteristics of oral tuberculosis differ from other pathologies in the oral mucosa According to Kakisi et al, the secondary form is observed more often than the primary one. 6 The oral focus of infection, M. Tuberculosis, may appear as a result of autoinfection from the sputum with a route of hematogenous or lymphatic transmission.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Additionally, the clinical characteristics of the lesion aids in differentiating it from other pathologies in the oral mucosa such as syphilis, histoplamosis, planoepithelial cancer, or recurrent or aphthous stomatitis. [9][10][11] Our finding is related to that reported by Krawiecka and Szponar et al 14 and Erbaycu et al, 15 who considered that the clinical characteristics of oral tuberculosis differ from other pathologies in the oral mucosa According to Kakisi et al, the secondary form is observed more often than the primary one. 6 The oral focus of infection, M. Tuberculosis, may appear as a result of autoinfection from the sputum with a route of hematogenous or lymphatic transmission.…”
Section: Discussionsupporting
confidence: 78%
“…[2][3][4][5][6] The pathological recognition of this entity is important and its early diagnosis is necessary. [9][10][11] TB can infect all parts of the mouth such as soft and hard palate, uvula, buccal mucosa, gingiva, lips, tongue, maxilla, and jaw. [6][7][8][9][10][11] According to published research by various authors two types of oral TB are recognized: primary oral TB which is more common in young patients and causes enlarged lymph nodes and secondary oral TB which is registered in adults of middle and advanced age with M. tuberculosis infecting buccal mucosa, gingival mucosa, tongue, lingual frenulum, and lips.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] In primary oral tuberculosis, the organisms are directly inoculated in the oral mucous membrane of a person who has not been infected. [7] Primary oral TB is observed more commonly in children and adolescents. [7] Oral manifestations of tuberculosis are quite rare due to the inability of Mycobacterium tuberculosis to invade the intact mucosa of oral cavity or pharynx.…”
Section: Resultsmentioning
confidence: 99%
“…[7] Primary oral TB is observed more commonly in children and adolescents. [7] Oral manifestations of tuberculosis are quite rare due to the inability of Mycobacterium tuberculosis to invade the intact mucosa of oral cavity or pharynx. Cleansing action of saliva, the presence of salivary enzymes, tissue antibodies, oral saprophytes and the thickness of the protective epithelial covering have been proposed as the underlying mechanism.…”
Section: Resultsmentioning
confidence: 99%